FAKTOR TEKANAN INSTITUSIONAL DALAM MEMENGARUHI KUALITAS INFORMASI AKUNTANSI: PENDEKATAN METODA CAMPURAN - Dwi Winarni; Rusdi Akbar (JURNAL AKUNTANSI, 2020)
Government financial statements, either from the central government or local government was obliged to gain an unqualified opinion from the Audit Board of Indonesia. However, although the government had gained it, based on investigation on the financial statements, the Audit Board of Indonesia still found some problems and concerned notes. Therefore, the researcher believed that further analysis on factors affecting accounting information quality was required. In accordance with previous research findings, there were several factors influencing such quality, i.e. external and internal institutional pressures that might have impacted the quality. Sample used was the secretaries and heads of finance subsection of all regional working units in the Local Government of Sleman. Research method used to explore the problems, map situational complexities, find out diverse participants’ perspectives, and observe the relationship among variables was the mix method. Research findings indicated strong evidence of the effects of external pressures on institutional internal factors. Furthermore, institutional internal factors positively affected accounting information quality; external pressures positively affected accounting information quality; while institutional internal factors mediated the effects of external pressures on accounting information quality.